Victimization and adversity among children experiencing war-related parental absence or deployment in a nationally representative US sample. (May 2017) - Turner, Heather A.; Finkelhor, David; Hamby, Sherry; Henly, Megan
Abstract: This study compares children and youth who have experienced lifetime war-related parental absence or deployment with those having no such history on a variety of victimization types, non-victimization adversity, trauma symptoms, and delinquency; and assesses whether cumulative adversity and victimization help to explain elevated emotional and behavioral problems among children of parents who have experienced war-related absence or deployment. The National Surveys of Children's Exposure to Violence (NatSCEV) are comprised of three cross-sectional telephone surveys conducted in 2008, 2011, and 2014. Data were collected on the experiences of children aged one month to seventeen years. In each survey, interviews were conducted with youth 10–17 years old and with caregivers of children 0–9 years old. The analyses use pooled data from all three U.S. nationally-representative samples (total sample size of 13, 052). Lifetime parental war-related absence or deployment was a marker for elevated childhood exposure to a wide array of victimization and adversity types. Cumulative past year exposure to multiple forms of victimization and adversity fully explained elevated trauma symptoms and delinquency in this population of children. Given the breadth of victimization and adversity risk, children with histories of parental war-related absence or deployment, as well as their families, represent important target groups for broad-based prevention and interventions to reduce exposure and ameliorate consequences when it does occur.